JOHN OSBORNE’S LOOK BACK IN ANGER: A CRITICAL CATCHES OF ANGER, ALIENATION AND ACRIMONY - ANURADHA SINGH (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2023)
The term “Angry Young Man” denoted the disillusionment and dilemma in young men which was caused by world war. The term represents the impatience with the tyranny laden over the lower/ middle strata of the society. At the time, John Osborne took the step to depict the frustration and alienation of young generation and created a protagonist, Jimmy Porter. The paper aims to analyses the character of Jimmy Porter by mapping the text based on real grounded society. The study is concentrated on the anger and fragmentation of not only of the protagonist but also of the whole society at a larger extent